Perceptions and Attitudes towards Medical Research in the United Arab Emirates: Results from the Abu Dhabi Cohort Study (ADCS) Focus Group Discussions - El Obaid, Yusra (PLoS One, 2016)
BACKGROUND: In developing medical research, particularly in regions where medical research is largely unfamiliar, it is important to understand public perceptions and attitudes towards medical research. In preparation for starting the first cohort study in the United Arab Emirates, the Abu Dhabi Cohort Study (ADCS), we sought to understand how we could improve the quality of the research process for participants and increase public trust and awareness of research. METHODS: We conducted six focus groups (FG), consisting of Emirati men and women aged above 18 years to resemble the target population for the ADCS. Sampling was purposive and convenient. Data collection was an iterative process until saturation was reached with no new themes identified. Text from each FG was analyzed separately by identifying emerging issues and organizing related concepts into categories or themes. A coding tree was developed, consisting of the main concepts, themes, subthemes and corresponding quotes. Both themes and main ideas were identified using inductive analysis. RESULTS: Forty-two participants enrolled at 3 academic centers (New York University Abu Dhabi, UAE University, Zayed University) and the Abu Dhabi blood bank. Focus group participants described lack of awareness of research as a challenge to participation in clinical research studies. Altruism, personal relevance of the research, and the use of role models were commonly identified motivators. Participants were generally satisfied with the informed consent process for the ADCS, but would be disappointed if not provided test results or study outcomes. Fear of a breach in confidentiality was a frequently expressed concern. CONCLUSIONS: Participants join research studies for varied, complex reasons, notably altruism and personal relevance. Based on these insights, we propose specific actions to enhance participant recruitment, retention and satisfaction in the ADCS. We identified opportunities to improve the research experience through improved study materials and communication to participants and the broader community.